Pancasila Value in Natural Disaster Management Based on Disaster Management - Erlinawati Erlinawati (Pancasila and Law Review, 2020)
The implementation of natural disaster management cannot be separated from Pancasila and the 1945 Constitution which underlies it. The values of Pancasila are explored and found from the values that have grown and lived in society, namely the values of divinity, humanity, unity, society and justice. In society these values remain valid and constitute a unified whole, inseparable and referring to one goal. This study aims to determine whether the values of Pancasila contained in Law Number 24 of 2007 concerning Disaster Management, and how the implementation of the values of Pancasila in natural Disaster Management. The research method used is empirical normative legal research with statute approach, this paper is descriptive, using primary data and secondary data are qualitative. The results of data analysis are discussed using the statute approach and conceptual approach. The result of the research is that Law Number 24 Year 2007 contains the values of Pancasila, namely the values of divinity, humanity, unity, society and justice. The values of humanity, society and justice, besides being explicitly mentioned in several articles, are also implicit in the articles. The value of God and unity is implied in several articles. The implementation of Pancasila values in natural disaster management in South Lampung Regency is manifested in the activities of disaster management, starting from pre-disaster, during emergency response and post-disaster.